2020
DOI: 10.1212/wnl.0000000000008687
|View full text |Cite
|
Sign up to set email alerts
|

Fetal loss and malformations in the MONEAD study of pregnant women with epilepsy

Abstract: ObjectiveTo examine occurrence of severe adverse fetal outcomes (SAO), including fetal loss and major congenital malformations (MCMs), in pregnant women with epilepsy (PWWE) vs healthy pregnant women (HPW).MethodsThe Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is an NIH-funded, prospective, observational, multicenter investigation of pregnancy outcomes for both mother and child, which enrolled women December 2012 through January 2016.ResultsThe 351 PWWE had 365 concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
2
19
4
4
Order By: Relevance
“…Recent data from the European and International Registry of Antiepileptic Drugs in Pregnancy (EURAP) showed that prevalence of MCMs in offspring exposed prenatally to AED monotherapy ranged from 2.8 % to 10.3 %, depending on the type of AEDs [15]. In the Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs study, adverse fetal outcomes including fetal loss and MCMs were significantly more common in WWE than in healthy pregnant women [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the European and International Registry of Antiepileptic Drugs in Pregnancy (EURAP) showed that prevalence of MCMs in offspring exposed prenatally to AED monotherapy ranged from 2.8 % to 10.3 %, depending on the type of AEDs [15]. In the Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs study, adverse fetal outcomes including fetal loss and MCMs were significantly more common in WWE than in healthy pregnant women [34].…”
Section: Discussionmentioning
confidence: 99%
“…15 In the Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs study, adverse fetal outcomes including fetal loss and MCMs were significantly more common in WWE than in healthy pregnant women. 33 In our study, the MCM rate was significantly lower in the planned-pregnancy group (1.6%) than in the unplanned-pregnancy group (7.5%). This decrease in MCMs rate could be partly because of the relatively less use of VPA, PB, phenytoin (PHT), CBZ, and topiramate (TPM) in the planned-pregnancy group than in the unplanned group.…”
Section: Discussioncontrasting
confidence: 47%
“…There were 45 retrospective 3,[5][6][7][8][9][10][13][14][15]19,20,[22][23][24][25] and 21 prospective 11, [16][17][18]21,26,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] cohort studies, 9 case-control studies, 4,12,75-81 and 1 cross-sectional study. 82 Sixty-two articles had a low risk of bias 3-11, 13-16, 18-26, 31-40, 42, 45, 46, 48, 50-60, 62-71,74-77,79 and 14 a high risk of bias 12,17,41,43,44,47,49,61,72,73,78,[80][81][82] (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%